Spatial genetic structure in wild cardoon, the ancestor of cultivated globe artichoke: Limited gene flow, fragmentation and population history. (December 2016) - Rau, D.; Rodriguez, M.; Rapposelli, E.; Murgia, M.L.; Papa, R.; Brown, A.H.D.; Attene, G.
Highlights: The population structure of wild cardoon (ancestor of globe artichoke) was analyzed. The species appears to be genetically fragmented over various spatial scales. This is due to gene dispersal, colonisation history and selective forces. To collect seeds from a few plants but many sites is the best gene sampling strategy. Abstract: Nuclear and chloroplast markers and phenotypic characters were integrated to analyse the population genetic structure of wild cardoon, Cynara cardunculus var. sylvestris, the ancestor of cultivated globe artichoke, Cynara cardunculus var. scolymus on the island of Sardinia, Italy. The spatial scale ranged from a few metres to ∼200 km. Wild cardoon appears to be genetically fragmented, with significant genetic divergence at various scales, indicating that gene flow is insufficient to counterbalance the effects of genetic drift or founder effects. Divergence between populations was higher for chloroplast (40%) than for nuclear markers (15%), suggesting that gene flow via seed was lower than via pollen. Two main genetic groups were detected; these correlated with differences in flowering time, capitula size, glossiness, and anthocyanin pigmentation. A complex population structure of wild cardoon emerged over small spatial scales, likely resulting from the interplay between gene dispersal, colonisation history and selective forces. Indeed, Sardinia appears to be a 'hybrid zone' of different gene pools. The island has unique diverse germplasm that has originated from hybridisation among different gene pools. The sampling of seeds from a few plants but from many sites is suggested as the best strategy to harvest the genetic diversity of wild cardoon.